Genomic epidemiology of Brucella suis biovar 2 in German swine and wildlife, 2003–2023 - Melzer, Falk; Linde, Jörg; Brangsch, Hanka (Frontiers in Veterinary Science, 2025)
IntroductionPorcine brucellosis, caused by Brucella suis biovar 2, is currently the only type of brucellosis officially reported in farm animals in Germany, with outbreaks confirmed through direct pathogen detection. In most European countries, this bacterial pathogen is also found in wild animals, which are considered reservoirs for the disease. Since 2003, 22 outbreaks of porcine brucellosis have been reported in Germany.MethodsA comprehensive study was conducted on German B. suis biovar 2 isolates obtained from routine diagnostic investigations of domestic pigs and wildlife. The dataset included isolates from 18 reported outbreaks. The aim was to assess epidemiological links and the genomic diversity of the bacterium. B. suis biovar 2 isolates were subjected to whole-genome sequencing (WGS) and analyzed using multilocus sequence typing (MLST), core genome MLST, and single-nucleotide polymorphism (SNP) analysis.ResultsThree different MLST sequence types were identified and further subdivided into eight clusters. This approach conclusively confirmed officially reported primary and secondary outbreaks caused by the sale of infected animals. In individual cases, remarkable similarities were found between domestic and wild animal isolates, that is, differing by only 2–4 nucleotides. This similarity suggests brucellosis transmission events. Both wild boars and hares can be considered reservoirs of Brucella spp. infections, including brucellosis. In Northern Germany, persistent B. suis biovar 2 foci were detected, as well as transmission across Germany and potentially to other European countries. Notably, hare isolates varied significantly from the majority of German wild boar and domestic pig isolates.DiscussionAs most brucellosis outbreaks occurred in outdoor holdings, reliable monitoring of these herds is recommended, although the exposure of these animals to external factors (e.g., vectors) poses a challenge. However, it is imperative in light of the increase in organic free-range and pasture farming, which promotes direct or indirect contact with wild animals.